Enhancing large-area scintillator detection with photonic crystal cavities - Ye, Wenzheng; Bizarri, Gregory; Birowosuto, Muhammad Danang; Wong, Liang Jie (American Chemical Society, 2022)
Scintillators are materials that emit visible photons when bombarded by high-energy particles (X-ray, γ-ray, electrons, neutrinos, etc.) and are crucial for applications, including X-ray imaging and high-energy particle detection. Here, we show that one-dimensional (1D) photonic crystal (PhC) cavities, added externally to scintillator materials, can be used to tailor the intrinsic emission spectrum of scintillators via the Purcell effect. The emission spectral peaks can be shifted, narrowed, or split, improving the overlap between the scintillator emission spectrum and the quantum efficiency (QE) spectrum of the photodetector. As a result, the overall photodetector signal can be enhanced by over 200%. The use of external PhC cavities especially benefits thick and large-area scintillators, which are needed to stop particles with ultrahigh energy, as in large-area neutrino detectors. Our findings should pave the way to greater versatility and efficiency in the design of scintillators for applications, including X-ray imaging and positron emission tomography.
Keywords: scintillators; nanophotonics; Purcell effect; spontaneous emission; high-energy particles